Effect of melphalan 140 mg/m2 vs 200 mg/m2 on toxicities and outcomes in multiple myeloma patients undergoing single autologous stem cell transplantation—a single center experience. Issue 8 (29th June 2016) - Katragadda, Lakshmikanth; McCullough, Lindsay M.; Dai, Yunfeng; Hsu, Jack; Byrne, Michael; Hiemenz, John; May, Stratford; Cogle, Christopher R.; Norkin, Maxim; Brown, Randy A.; Wingard, John R.; Chang, Myron; et al.
Abstract: Although melphalan at a dose of 140 mg/m 2 (MEL140) is an acceptable conditioning regimen for autologous stem cell transplantation (ASCT) in multiple myeloma (MM) patients, very few studies compared it to the most commonly used dose of 200 mg/m 2 (MEL200). A retrospective review of records of MM patients (2001–2010) identified 33 patients who received MEL140 and 96 patients who received MEL200. As expected, significantly higher percentage of patients in the MEL140 arm were >65 years or had cardiac ejection fraction <50%, had Karnofsky score <80, or had creatinine >2 at the time of ASCT ( P ≤.01). There were no significant differences in incidence of treatment related mortality and morbidity. At a median follow‐up of 74 months from ASCT, there were no significant differences in relapse free survival (RFS) and overall survival (OS) between the two groups. Similar proportion had myeloma status improve to ≥VGPR at 3 months post‐ASCT. Usage of post‐ASCT maintenance was similar. In multivariate cox proportional hazards model, only disease status of ≥VGPR at the time of ASCT significantly improved RFS ( P =.024), but not OS ( P =.104). In conclusion, MM patients who received MEL140 had similar long‐term outcomes to MEL200 patients despite their older age and co‐morbidities.